The Effects of Concentration and Fermentation Time on Quality of Local Microorganism Solutions (LMS) of Stale Rice, Cassava âTapeâ, Banana Bumps and Cowâs Rumen or Rotten Fruits - indasah, indasah; Peristiowati, Yuli; Nurwijayanti, Nurwijayanti (Health Notions, 2017)
The objective of this research was to analyze the quality of bioactivator from stale rice, cassava tape, banana bumps, cowâs rumen / rotten fruit, based on concentration and fermentation time, with factorial design. The first factor was the concentration of stale rice, tape, banana bumps, cowâs rumen or rotten fruit, which was 150 grams and 250. The second factor was fermentation time consisting of: F1 (Fermentation for 10 days), F2 (Fermentation for 20 days). Parameters observed were: total population of bacteria, pH and temperature. Data were analyzed using Anova. The results showed that the highest result of total bacterial population was found on 150 gram banana bumps with fermentation of 20 days ie 41 x 106 and the lowest on 150 gram cassava tape with 10 day fermentation that was 1x102. The highest pH was found on rice with 250 grams of fermented rice with 20 days of 3.00 and the lowest on 250 grams of banana bumps on day 0 which was 5.96. The highest temperature on stale rice was 150 gram with 10 days fermentation, 150 banana bumps and 250 gram with 10 day fermentation of 29.5 0C and the lowest temperature on 150 gram cassava tape, rumen / rotten fruit of 150 gram on day 0 was 27 0C. Anova analysis showed no difference in the number of germs from the eight groups.